DREDGING IMPACT ON THE LAKE MANZHEROK (REPUBLIC OF ALTAY) HYDRO/ BIOLOGICAL AND SANITARY/MICRO/BIOLOGICAL CHARACTERISTICS - Dmitry M. Bezmaternykh; Vladimir V. Kirillov; Nadezhda I. Yermolaeva; Laura M. Kipryanova; Lyubov V. Yanygina; Elena Y. Mitrofanova; Olga N. Vdovina; Anton V. Kotovschikov; Evgeniya Y. Zarubina (Водное хозяйство России: проблемы, технологии, управление)
The article assesses ecological status of the Lake Manzherok (Republic of Altay Mayminsk Rayon) by its hydro/biological and sanitary/micro/biological characteristics after completion of dredging works. To estimate the bio/ceonosis dynamics we used the archive data of 2007–2015 and references. The aquatic communities demonstrated low indicators of development, phytoplankton – 26 taxons, abundance did not exceed 1.3·103 thousand cells/m3, biomass did not exceed 64.0·10-3 mg/m3. In water we found the sapropel vegetative pigments with the chlorophyll a of 237 mg/m3. We identified 16 species of zooplankton with 3.5–18.2 thousand pieces/m3 abundance with 23.4–97.3 mg/m3 biomass. In comparison with 2015 the filtering zooplankton organisms’ abundance and biomass were 10–15 times lower. In contrast with 14–15 species in previous years we identified 5 species of macrophytes. The benthos abundance was not more than 1.48 thousand pieces/m2, the biomass did not exceed 1.56 g/m2, that is lower than in 2007. Such low indicators of the aquatic communities’ development with high concentration of organic matter argue the temporal state of anthropogenic metabolic regress. The Lake Manzherok water quality by its sanitary/micro/biological characteristics did not agree with the requirements to recreational water bodies. The whole content of coliform bacteria in the off-shore zone 25 times exceeded the norm, while the content of thermo/tolerant coliform bacteria in the center of the lake and in the macrophytes tangle 2.3 times exceeded the norm.